2012
DOI: 10.1103/physrevlett.109.081101
|View full text |Cite
|
Sign up to set email alerts
|

Minimagnetospheres above the Lunar Surface and the Formation of Lunar Swirls

Abstract: In this paper we present in-situ satellite data, theory and laboratory validation that show how small scale collisionless shocks and mini-magnetospheres can form on the electron inertial scale length. The resulting retardation and deflection of the solar wind ions could be responsible for the unusual "lunar swirl" patterns seen on the surface of the Moon.Miniature magnetospheres have been found to exist above the lunar surface [1] and are closely related to features known as "lunar swirls" [2]. Mini-magnetosph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 21 publications
7
53
0
Order By: Relevance
“…The electric field responsible for the scattering can be seen to be omnidirectionally pointing outward, regardless of the magnetic field orientation. This is because it is proportional to the gradient in the magnetic field intensity, | |  B 2 , not | | B , in accordance with theoretical expectations (Bamford et al 2012). The projection onto the x−y or surface plane shows the electric field intensity at the lunar surface.…”
Section: The Simulationssupporting
confidence: 84%
See 4 more Smart Citations
“…The electric field responsible for the scattering can be seen to be omnidirectionally pointing outward, regardless of the magnetic field orientation. This is because it is proportional to the gradient in the magnetic field intensity, | |  B 2 , not | | B , in accordance with theoretical expectations (Bamford et al 2012). The projection onto the x−y or surface plane shows the electric field intensity at the lunar surface.…”
Section: The Simulationssupporting
confidence: 84%
“…The simulations quantifiably confirm the satellite (Halekas et al 2014) findings and the theoretical predictions (Bamford et al 2012), namely that a miniature collisionless shock can be responsible for all the observations (Lin et al 1998;Huixian et al 2005;Wieser et al 2009Wieser et al , 2010Futaana et al 2010;Hashimoto et al 2010;Lue et al 2011;Wang et al 2012;Halekas et al 2014;Yokota et al 2014). Here it is confirmed that the interaction or boundary layer can form well above (i.e., kilometers rather than meters) the lunar surface (depending upon conditions) and need not be a photoelectricsheath (Garrick-Bethell et al 2011) restricted to a few meters above the surface.…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations